Efficient development and reuse of domain–specific languages for automation systems. (7th July 2014) - Preschern, Christopher; Kajtazovic, Nermin; Kreiner, Christian
Domain–Specific Languages (DSLs) help to decrease system development costs by providing developers with an effective way to construct systems for a specific domain. However, for DSL construction, a developer has to invest some upfront investment. If this investment is smaller than the benefit in terms of more effective development for domain–specific systems, then the construction of a DSL pays off. In order to decrease the initial effort to construct DSLs for a specific domain (the automation domain), we present an efficient DSL architecture which allows structured reuse within the automation domain. With this DSL architecture, it is easier to build an initial automation DSL and when building multiple automation DSLs, significant parts of the DSL can be reused across different automation domains. We present the DSL architecture and discuss its benefits and drawbacks. Furthermore, we present and evaluate three automation DSL case studies which apply the described architecture.